The spatial distribution of unique motifs featuring Dioscorea bulbifera, the round yam, in western Arnhem Land rock art. Issue 2 (4th May 2019) - Hammond, Judith W
Abstract: A distinctive subset of plant-related motifs has been identified amongst the assemblage of Yam Figure style rock paintings in western Arnhem Land. Named the Type I phyto-motif, its form is based on botanical attributes of the round yam, Dioscorea bulbifera, which differs from other yam motifs in northern Australia. The current study analyses the spatial distribution of Type I phyto-motifs and establishes that they occur predominantly along the lowland valley of Deaf Adder Creek. This locality contrasts with the core type area on the higher western section of the Arnhem Land Plateau where most other Yam Figure style sites are found. The Type I phyto-motif subset appears to represent a discrete cultural tradition amongst the Yam Figure assemblage - one separate from that of panels depicting the composite Rainbow Snake with accompanying yam motifs.